2D Thick-Section MR Digital Subtraction Angiography for the Assessment of Dural Arteriovenous Fistulas - Horie, N.; Morikawa, M.; Kitigawa, N.; Tsutsumi, K.; Kaminogo, M.; Nagata, I. (American Journal of Neuroradiology, 2006)
BACKGROUND AND PURPOSE: Although dynamic contrast-enhanced MR angiography studies for arteriovenous malformations (AVFs) and brain tumors have shown promising results, no formal attempt has yet been made to similarly evaluate dural AVFs. To assess the practical applicability of 2D thick-section contrast enhanced MR digital subtraction angiography (MRDSA) for the diagnosis and management of dural AVFs, MRDSA and intra-arterial digital subtraction angiography (IADSA) were comparatively evaluated.METHODS: We performed 80 consecutive MRDSA studies for 25 dural AVFs, including 11 cavenous sinuses, 9 sigmoid sinuses, 2 tentorial sinuses, one anterior condylar vein, one craniocervical junction, and one spine. MR images were continuously obtained following the initiation of a bolus injection of gadrinium chelates and subtraction images were constructed. We thereafter evaluated the imaging quality and hemodynamic information from all 46 MRDSA images performed in parallel with IADSA in either perioperative or follow-up studies.RESULTS: Most MRDSA images detected early venous filling, sinus occlusion, leptomeningeal venous drainage, and varices. It was difficult, however, to identify the feeding arteries because of both the partial volume effect and a low spatial resolution. Most important, MRDSA accurately detected aggressive lesions with leptomeningeal venous drainage and varices.CONCLUSION: Our MRDSA technique was found to have limited value for depicting all the anatomic details of dural AVFs, though it was able to identify important hemodynamic abnormalities related to the risk of hemorrhaging. MRDSA is therefore useful as a less invasive, dynamic angiographic tool, not only for perioperative studies but also for follow-up studies.